2014
DOI: 10.1016/j.yhbeh.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

On the value of seasonal mammals for identifying mechanisms underlying the control of food intake and body weight

Abstract: This article is part of a Special Issue “Energy Balance”.Seasonal cycles of adiposity and body weight reflecting changes in both food intake and energy expenditure are the norm in mammals that have evolved in temperate and polar habitats. Innate circannual rhythmicity and direct responses to the annual change in photoperiod combine to ensure that behavior and energy metabolism are regulated in anticipation of altered energetic demands such as the energetically costly processes of hibernation, migration, and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 126 publications
1
58
0
Order By: Relevance
“…Even in longterm high-fat diet studies where some increase in food intake can be observed in Siberian hamsters, this does not result in weight gain, rather the animals increase thermogenesis via increased sympathetic nervous system (SNS) activation of brown fat (McElroy et al 1986). Although hamsters have a different biology from mice and rats, which is a reflection of their evolution and ecology, they cannot be considered to be any less valid as a model for understanding fundamental mechanisms of action of hormones than other rodents; indeed, using a variety of animal models has overall translational benefits (Ebling 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in longterm high-fat diet studies where some increase in food intake can be observed in Siberian hamsters, this does not result in weight gain, rather the animals increase thermogenesis via increased sympathetic nervous system (SNS) activation of brown fat (McElroy et al 1986). Although hamsters have a different biology from mice and rats, which is a reflection of their evolution and ecology, they cannot be considered to be any less valid as a model for understanding fundamental mechanisms of action of hormones than other rodents; indeed, using a variety of animal models has overall translational benefits (Ebling 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Siberian hamster (Phodopus sungorus) is a natural animal model of adaptive adiposity, which can be experimentally induced via a change in photoperiod to increase or decrease appetite and body weight (Ebling 2014). Their summer state is induced by long day lengths and is characterized by increased adiposity coupled with leptin resistance and elevated plasma insulin concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…As described in a companion paper in this special issue of Hormones and Behavior , many species show seasonal changes in food intake and energy utilization that are regulated by thyroid hormone availability (Ebling, 2014). In addition, social-cognitive factors can facilitate or inhibit food intake independent of satiety- or hunger-inducing signals (Cohen, 2008; Zheng and Berthoud, 2007) and these may account for some of the variance in rates of obesity in human populations (Berthoud, 2012; Booth and Booth, 2011).…”
Section: Regulation Of Food Intakementioning
confidence: 99%
“…However preliminary evidence from experiments in the European quail (Coturnix coturnix) suggested that AGRP and POMC gene expression were unchanged at a time when food intake and body mass were increasing during the migratory period (Cornelius et al, 2013). These findings are reminiscent of those from studies of seasonal mammals where the rheostatic mechanisms appear to lie in brain areas outside the arcuate nucleus (Ebling, 2014). Another example of rheostasis that has been well defined in birds is the voluntary loss of appetite and body mass that occurs during incubation, one of several examples of naturally occurring 'animal anorexias' (Savory, 1979;Sherry et al, 1980;Mrosovsky and Sherry, 1980).…”
Section: Seasonal and Stress-induced Changes In Body Massmentioning
confidence: 77%